An Emergency Department Audit - Pandey, Bandana (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Introduction:Regular and well conducted clinical audit helps clinicians improve services. Clinical audit, with timely feedback to all staff, is one of the most powerful tools available to assess, and therefore to drive improvements in the quality, safety, consistency for urgent and emergency care. Method: Data were collected over six months (1stBaisakh 2068 to 30th Asoj 2068) from medical register of department of emergency, Kathmandu medical college. Demography, emergency clinical diagnosis and management were analyzed. Result: Total 3605 cases attended over 6 months period in emergency department of Kathmandu Medical College Teaching Hospital (KMCTH). Most cases (57%) were medical cases followed by surgical (27%), Obstetrics/Gynecology, Orthopedics, Pediatrics (3% each) and psychiatry, neurosurgery, ENT (2% each). Conclusion: Emergency audit represents status of hospital in society. It guides Management to improve and expand faculties.